Titus Andronicus - Shakespeare, William, 1564-1616 (Salt Lake City, UT : Project Gutenberg, 1997)
"Titus Andronicus" by William Shakespeare is a tragedy written between 1588 and 1593. Roman general Titus returns victorious from war with Tamora, Queen of the Goths, as his prisoner. When he sacrifices her son and she becomes empress, Tamora vows revenge. What follows is a brutal cycle of violence involving murder, mutilation, and unspeakable acts of retribution. Shakespeare's first tragedy shocked audiences with its graphic bloodshed and remains his most violent work$1 (Ba dark exploration of vengeance spiraling beyond control. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Titus_Andronicus
The First Folio, 1623
Release date is 1997-11-01
Keywords: Tragedies (Drama); Andronicus, Titus (Legendary character) -- Drama; Goths -- Drama; Generals -- Drama; Rome -- History -- Germanic invasions, 3rd-6th centuries -- Drama; Historical drama